(untitled) (Innovative professional education, 2024)
In the system of professional advanced design education, more attention should be paid to diversifying the forms of development of professional and entrepreneurial competences. Analyzing the pedagogical practice of VSP "FKMD KNUTD" (Kyiv), we believe that extracurricular design projects as a means of actualizing individual creative qualities and an impetus to independent design activity can effectively and holistically develop the specified competencies, which are the key to the development of small business and will a necessary condition for the post-war reconstruction of the country’s economy.